Understanding Teachers’ Computer Anxiety - Maria Christina Eko Setyarini (ETERNAL (English Teaching Journal), 2015)
The rapid development of ICT has impacted language education in such a way that teachers are required to be proficient in computer technology. However, there is a fact that many teachers still experienced computer anxiety which can hinder the teachers in achieving the proficiency level required. This study aimed at finding explanations about computer anxiety experienced by English teachers in Indonesian context. 32 English teachers from Salatiga were given a questionnaire adapted from Koltrik and Redmann (2009)’s questionnaire to measure their level of computer anxiety. Subsequently, 14 of the participants who have moderate to very high anxiety were interviewed. The result of the studies shows that the teachers experienced computer anxiety with various psychological and physical symptoms. The computer anxiety was caused by four categories of factors namely social matter, psychological matter, teachers’ ability and technical matters. The study also revealed that the teachers had thought of strategies to cope with the computer anxiety. They are alternative action, social solution, individual preparation, self-motivation, and facility provision. The findings of the study is expected to be useful for those who wish to understand more about computer anxiety and those who are struggling with computer anxiety.